The Impact and Safety of GLP‐1 Agents and Breast Cancer - Kayla Parsons; Mateo Montalvo; Neal Fischbach; Melissa Taylor; Salome Alfaro; Maryam Lustberg (Cancer Medicine, 2025)
ABSTRACT Introduction Obesity and breast cancer rates are increasing globally, with obesity prevalence more than doubling since 1990. By 2022, 44% of women were overweight, and 18% were obese. Breast cancer remains the most common malignancy among women, with 2.2 million new cases in 2020. A significant proportion of breast cancer patients are overweight or obese at diagnosis, which is associated with higher recurrence and mortality rates. Recently, GLP‐1 receptor agonists (GLP‐1 RAs) have emerged as remarkably effective weight loss drugs. Understanding the relationship between obesity, breast cancer, and weight loss is crucial for improving patient outcomes. Methodology A comprehensive review of literature from 1996 to 2024 was conducted using databases such as PubMed, Medline, and Web of Science. Studies included epidemiological data on obesity and breast cancer incidence, systematic reviews, meta‐analyses, and clinical trials on weight management interventions (behavioral modification, bariatric surgery, and pharmacological treatments) for breast cancer patients. Preclinical studies examining the biological mechanisms linking obesity and breast cancer progression were also reviewed. Results Epidemiological studies consistently show that overweight and obese post‐menopausal women have an increased risk of developing breast cancer. Obesity at diagnosis is linked to worse outcomes, including higher disease recurrence, breast cancer‐specific mortality, and all‐cause mortality. Weight gain during treatment, particularly with chemotherapy, is common and often leads to sarcopenic obesity. Behavioral interventions have shown modest weight loss but are difficult to maintain. Bariatric surgery reduces the risk of developing breast cancer but lacks data on its impact on tumor characteristics and recurrence. GLP‐1 receptor agonists like semaglutide and tirzepatide have demonstrated significant weight loss in non‐cancer populations, but their safety and efficacy in breast cancer patients are not well established. Discussion The biology underlying obesity's role in breast cancer progression involves complex interactions between adipocytokines, hormones, and inflammatory cytokines. Weight loss interventions have potential benefits, but sustaining weight reduction in breast cancer patients is challenging. The emerging pharmacological treatments, particularly GLP‐1 receptor agonists, show promise for effective weight management but require further investigation to confirm their safety and impact on breast cancer outcomes. Conclusion Addressing obesity in breast cancer patients is critical for improving prognosis and quality of life. While current data do not suggest adverse safety signals with GLP‐1 receptor agonists, more research is needed to fully understand their effects. Effective, safe, and sustainable weight management strategies are urgently needed to support breast cancer patients.